Uma cartografia de vivências e desejos femininos: conversando com jovens do distrito de retiro, Coração de Maria - Ba - Costa, Adriane Gomes Araujo (2022)
his Cartography was built in two stages, the first sought to know the ways how the gender and sexuality relations are constructed among young women of rural District of Retiro of the county Coração de Maria, Bahia; the second, how those gender relations influence their experiences and the construction and experimentation of desire. This research has a qualitative nature, combining the theoretical-methodological references of the Cartography and the Netnography, incorporating the logbook and Google Meet as fundamental tools to conduct the research that happened during the social isolation due to the COVID-19 pandemic. We reflected about the relation between self-esteem and the influence of the media and how the beauty industry has influenced and built uniform patterns that ignore the difference as an intrinsic element of the living beings. We identified the visible and invisible barriers that have permeated the construction and realization of our desires. Besides that, an important question: is there space for those desires or do we need to reclaim them? The field of the desires still are under constant vigilance and punishment. The becoming-feminine is a potency of desires that, under the domination of the colonizing notion that refuses the different, was put under constant punishment. But that doesn't prevent us from continuing to identify the markers that delimit our sexuality and everything that comes after and with it. This Cartography mapped the constructions of the feminine becomings, full of subjectivity and desire, and how they are experiencing the world.